Application of ERT, IP and VLF-EM Methods to Investigate Landslide-Prone Structures at Archaeological Sites in Lamreh, Aceh Besar, Indonesia - Ali, Bukhari; Nanda, Muhammad; Zainal, Muzakir; Yanis, Muhammad; Surbakti, Muhammad Syukri; Idris, Nasrullah; Ismail, Nazli (Trends in Sciences, 2024)
Since the 21st century, Lamreh, Aceh Besar Regency, Indonesia played an important role during the maritime silk route at the gate of the Malacca strait. This article investigates the subsurface structure of landslide-prone areas in cultural heritage based on 2D resistivity, chargeability and current density models of ERT, IP and VLF-EM methods, respectively. Field data measurements were carried out on 2 crossing profiles along the cliff suspected of experiencing landslides. The length of each profile is 220 with 4 m distance between stations. The 2D models reveal that the subsurface geological structure of Lamreh is composed of a mixed layer of clastic sediment and volcanic material at the top, followed by a layer of calcareous sandstone, and volcanic breccia at the bottom. The 3 layers are most easily distinguished in the resistivity model. The topmost layer is permeable but dry, i.e., characterized by a more resistive layer in the models. While the second layer is characterized by an intermediate conductivity and the bottom layer is highly conductive. The conductivity in these 2 layers is influenced by the degree of water content within the rocks. The chargeability models derived from IP data can distinguish between the dry layer on the surface and the saturated layer below. Meanwhile, the current density models obtained from VLF-EM data have proven the presence of fractures and faults along the profiles due to weathering as also seen in the resistivity models. HIGHLIGHTS Investigation of subsurface structure in landslide-prone area of Lamreh, Aceh Besar Regency, Indonesia, a cultural heritage site with historical significance in the maritime silk route. Utilization of 2D resistivity, chargeability and current density models (ERT, IP and VLF-EM) to analyze the subsurface structure. Field data measurements conducted on 2 crossing profiles along the suspected landslide cliff, with a profile length of 220 and 4 m station distance. Subsurface geological structure of Lamreh identified as a mixed layer of clastic sediment and volcanic material at the top, followed by calcareous sandstone and volcanic breccia at the bottom. Resistivity models most effectively distinguish the 3 layers, highlighting permeable but dry top layer, intermediate conductivity in the second layer, and high conductivity in the bottom layer influenced by water content. Chargeability and current density models confirm surface dryness and presence of fractures and faults due to weathering GRAPHICAL ABSTRACT